Teaching Project Based Learning in English for Specific Purposes - Dwi Wulandari (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
English course in Diponegoro University as the basic required course is offered mostly by the department without giving any prior consideration of its purpose, and mostly arranged by the teachers without any guidance from the departments. This study is conducted with the purpose to see the possibility of teaching English by focusing the materials on students’ main competence and emphasized on student centered learning. The action research is targeted on having students use their English in demonstrating their main competence both in speaking and writing, through the method of Project Based Learning. The result shows that students are more motivated to study English and that it helps students to take the benefit of learning English for the development of their main competence. The further benefit is that students are able to increase their ability in academic writing and that they have more confident in speaking English. The main drawback from the study is that the groups work well to help students work more completely and easily, however it is true that since the works are mostly in group, individual problem may not be easily catered.